خلع فسخ نکاح ہے یا طلاق فقہائے کرام کی آراء کا تجزیاتی مطالعہ: Whether Khula is Dissolution of Marriage or Divorce Critical Analysis of the Views of Islamic Jurists - Shah, Hafiz Muhammad Mearaj (Al-Amīr Research Journal for Islamic Studies, 2022)
Islam is an entire way of life. It illuminates every facet of daily existence. There is no problem for which Islam has not provided a remedy. Every aspect of beliefs and ethics, including human affairs, has also been examined. Islam is the only religion on earth that can be compared the height of Western culture and civilization. People have become its slavish disciples in the most literal sense. To stay up with the rest of the world, they are creating new interpretations of Islam for this reason. Accepted wisdom is a benefit, but only within the bounds of Sharia. Otherwise, it is Shaytan's legacy. ۔(شیطان) One of the most significant and crucial stages in a person's life is the nikah. It is expressly covered in the Qur'an and Hadith. It is created necessary for sustaining human existence. It is referred to as the culmination of human life and one of the Prophet's (ﷺ) required Sunnas. However, one of the most despised actions is the dissolution of a marriage. Islam, however, differs from other faiths. It contains the entire procedure/laws for dissolving a marriage. The appropriate discussion of Talaq and Khula is illustrated by the jurists' use of Estihsan and Qayas. Recent years have seen various crises and a collapse in Pakistani society. Smear and family system disturbance are the main issues among them. "Nikkah" is the fundamental element of a family system; in reality, a family system is based on Nikkah. If this Nikkah is intact, the entire family system is stable; nevertheless, if this Nikkah is broken, not only is the family system traumatised, but the entire society begins to suffer. The summary of this thesis explains that the Islamic Ideological Council's recommendations have been reviewed in light of the non-Sharia practises of the judicial authorities in relation to Khula and judicial powers related to Khula, as well as an analytical study of the remarks and opinions of commentators and jurists, including future jurists, regarding Khula. Key Words: Khul‘a, Judicial Khul‘a, Tansīkh e Nikaḥ, Divorce, ‘Īddat.